1960
DOI: 10.1039/tf9605601144
|View full text |Cite
|
Sign up to set email alerts
|

Vapour diffusion coefficients and collision parameters for cyclic molecules

Abstract: Measurements are reported on the inter-diffusion coefficients of benzene, thiophen, pyridine, piperidine and ietrahydrothiophen vapours in binary systems with hydrogen, nitrogen and oxygen. Previously published results on diffusion coefficients for cyclohexane and on the viscosities of the vapours together with new viscosity measurements for piperidine and tetrahydro-thiophen have been combined with the diffusion data to evaluate collision diameters for this family of cyclic molecules.Assuming collision diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1961
1961
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…(9) do not take into account the effects of different structures of isomers, which may have different collisional cross sections and thus different diffusion volumes. The measured (Cummings and Ubbelohde, 1953;Cummings et al, 1955;Hudson et al, 1960;Altshuller and Cohen, 1960;Nagata and Hasegawa, 1970) and estimated diffusivities of four isomers (cyclohexane, methyl cyclopentane, 1-hexene, and 2,3-dimethyl-2butene) of C 6 H 12 are listed in Table A1 in the Appendix, showing good agreement between measured and estimated values. This suggests that the effect of different isomers may be of minor importance.…”
Section: Estimation Of Gas Phase Diffusivitiesmentioning
confidence: 79%
See 1 more Smart Citation
“…(9) do not take into account the effects of different structures of isomers, which may have different collisional cross sections and thus different diffusion volumes. The measured (Cummings and Ubbelohde, 1953;Cummings et al, 1955;Hudson et al, 1960;Altshuller and Cohen, 1960;Nagata and Hasegawa, 1970) and estimated diffusivities of four isomers (cyclohexane, methyl cyclopentane, 1-hexene, and 2,3-dimethyl-2butene) of C 6 H 12 are listed in Table A1 in the Appendix, showing good agreement between measured and estimated values. This suggests that the effect of different isomers may be of minor importance.…”
Section: Estimation Of Gas Phase Diffusivitiesmentioning
confidence: 79%
“…Temperatures of tropospheric and stratospheric interest range from ∼ 200 to ∼ 300 K. However, most of the diffusivity measurements were only carried out at around room temperature. For those studies in which the effect of tempera- ture was investigated, they were usually performed at temperatures > 300 K. The measured diffusivities of 2-propanol (Gilliland, 1934;Lugg, 1968;Arnikar and Ghule, 1969;Nagata and Hasegawa, 1970), benzene (Lee and Wilke, 1954;Hudson et al, 1960;Altshuller and Cohen, 1960;Getzinger and Wilke, 1967;Lugg, 1968;Katan, 1969;Arnikar and Ghule, 1969;Nagata and Hasegawa, 1970), n-pentane (Lugg, 1968;Barr and Watts, 1972;Nagasaka, 1973), and ethyl formate (Lugg, 1968;Nagata and Hasegawa, 1970) are plotted as a function of temperature in Fig. 1, together with the estimated diffusivities (black curves) using Fuller's method.…”
Section: Temperature Dependencementioning
confidence: 99%
“…If the surface diffusion of the adsorbed molecule is to be studied fundamentally, then it seems logical to investigate and analyze the gas-solid interaction energy for the system. There are some publications (2, 3,6,7,12,14) which deal with the calculation of the dispersion energy for both homogeneous and heterogeneous systems. However, no one has attempted to apply those techniques to the study of surface diffusion.…”
Section: University Of Lowo Iowa City Lowomentioning
confidence: 99%
“…Values of the second virial coefficient B, of the gas mixtures were reported over a range of temperature and it was shown that these values lie quite close to those obtained by the use of their corresponding states equation (eqn. (4)), together with the combining rules ( 6) and ( 7) and the geometric mean rule for Tt2 (eqn. ( 8)).…”
Section: C G L a S H A N A N D Pottermentioning
confidence: 99%